1997
DOI: 10.1002/pro.5560060719
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the BPTI folding pathway: I. Effects of aromatic → leucine substitutions on the distribution of folding intermediates

Abstract: The roles of aromatic residues in determining the folding pathway of bovine pancreatic trypsin inhibitor (BPTI) were analyzed mutationally by examining the distribution of disulfide-bonded intermediates that accumulated during the refolding of protein variants in which tyrosine or phenylalanine residues were individually replaced with leucine. The eight substitutions examined all caused significant changes in the intermediate distribution. In some cases, the major effect was to decrease the accumulation of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 74 publications
2
28
0
Order By: Relevance
“…We suggest that Tyr-116, perhaps through resonance effects, facilitates formation of the Cys-59/ Sec-498 intermediate selenenylsulfide by weakening the C-terminal selenenylsulfide bond in its oxidized state. It is a well known phenomenon that tyrosine residues can affect the formation and/or reactivity of dithiol/disulfide motifs, such as in the active sites of glutaredoxins (66) or during formation of folding intermediates (67). In other words, we propose that the interaction of the side chain of Tyr-116 with Sec in the selenenylsulfide of the oxidized C terminus may weaken this bond (increase its inherently low redox potential), so that its reduction by the N-terminal dithiol/chargetransfer complex becomes facilitated.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that Tyr-116, perhaps through resonance effects, facilitates formation of the Cys-59/ Sec-498 intermediate selenenylsulfide by weakening the C-terminal selenenylsulfide bond in its oxidized state. It is a well known phenomenon that tyrosine residues can affect the formation and/or reactivity of dithiol/disulfide motifs, such as in the active sites of glutaredoxins (66) or during formation of folding intermediates (67). In other words, we propose that the interaction of the side chain of Tyr-116 with Sec in the selenenylsulfide of the oxidized C terminus may weaken this bond (increase its inherently low redox potential), so that its reduction by the N-terminal dithiol/chargetransfer complex becomes facilitated.…”
Section: Discussionmentioning
confidence: 99%
“…Aprotinin was dissolved in the same buffer solution. The Y35G BPTI protein was produced by heterologous expression in Escherichiacoli and purified as described previously (61 Crystals were soaked briefly in reservoir solution plus 20% (v/v) ethylene glycol as cryoprotectant prior to freezing in liquid propane at 100 K. During data collection, crystals were maintained at 100 K in a stream of evaporated nitrogen (Oxford Cryosystems). Data were collected with use of a CCD detector and a rotating anode FR591 generator (Nonius Delft, Netherlands).…”
Section: Crystallographymentioning
confidence: 99%
“…These substitutions were distributed throughout the sequence of the protein and have been found to cause a variety of effects on the stability of the native protein or the major one-disulfide intermediate, @30-51# Goldenberg et al, 1989Goldenberg et al, , 1992, 1997a, 1997b!. The reaction rates for these proteins are compared in Fig-ure 3B.…”
Section: Reactivities Of Cysteine Thiols In Reduced Bptimentioning
confidence: 99%
“…These experiments revealed that only a fraction of the possible disulfidebonded intermediates accumulate to significant levels during refolding, thus providing some of the first experimental evidence to support the view that proteins fold via specific pathways. In subsequent studies, a variety of techniques, including NMR spectroscopy and mutational analysis, have been used to analyze the conformations of the intermediates and the interactions that stabilize them~Goldenberg et al, 1989;van Mierlo et al, 1991avan Mierlo et al, , 1991bvan Mierlo et al, , 1993van Mierlo et al, , 1994Staley & Kim, 1992Yu et al, 1995;Zhang & Goldenberg, 1997a, 1997b!. Although there have been significant disagreements about the relative importance of intermediates with native and non-native disulfides, there is general agreement that the steady-state distribution of intermediates is dominated by species with only native disulfides, but that intermediates with nonnative bonds also play important kinetic roles in the process of forming the native protein~Weissman & Kim, 1991Creighton, 1992;Darby et al, 1995!. The initial steps in the refolding of reduced BPTI quickly lead to a steady-state distribution of one-disulfide intermediates, and this distribution is dominated by one or two species~depending on Reprint requests to: David P. Goldenberg, Department of Biology, University of Utah, 257 South 1400 East, Salt Lake City, Utah 84112-0840; e-mail: goldenberg@biology.utah.edu.…”
mentioning
confidence: 99%